In vitro micropropagation of Alpinia zerumbet Variegate, an important medicinal plant, through rhizome bud explants - Rakkimuthu, R.; Jacob, Jinu; Aravinthan, K. M. (Research in Biotechnology, 2011)
An ideal Micropropagation method of Alpinia zerumbet has been developed using rhizome bud explants. Basal MS medium supplemented with 3% sucrose (w/v) different concentrations of BAP in combination with 0.5 mg / L of kinetin. Highest percentage (95%) of explants for shoot induction and multiple shoot (7.9 per explants) production were observed in theÃ‚Â  combination of 1.5 mg / L of BAP, 0.5 mg / L of kinetin. In this case, all the inoculated explants induced multiple shoots within 6-7 weeks of inoculation. Rooting was induced in a medium having half strength MS supplemented with 0.5mg / L of IBA. Most of the generated shoots were successfully transferred to soil under field conditions.